Self‐Assembly of Lamellae‐in‐Lamellae by Double‐Tail Cationic Surfactants - Zhixuan Zhong; Guanqun Du; Linbo Ma; Yilin Wang; Jian Jiang (Advanced Science, 2024)
Abstract The molecular structures of surfactants play a pivotal role in influencing their self‐assembly behaviors. In this work, using simulations and experiments, an unconventional hierarchically layered structure in the didodecyldimethylammonium bromide (DDAB)/water binary system: lamellae‐in‐lamellae is revealed, a new self‐assembly structure in surfactant system. This self‐assembly structure refers to a lamellar structure with a shorter periodic length (inner lamellae) embedded in a lamellar phase with a longer periodic length (outer lamellae). The normal vectors of these two lamellar regions orient perpendicularly. In addition, it is observed that this lamellar‐in‐lamellar phase disappears when the two tails of the cationic surfactants become longer. The formation of the lamellar‐in‐lamellar architecture arises from multiple interacting factors. The key element is that the short tails of the DDAB surfactants enhance hydrophilicity and rigidity, which facilitates the formation of the inner lamellae. Moreover, the lateral monolayer of the inner lamellae provides shielding from the water and prompts the formation of the outer lamellae. These findings indicate that molecular structures and flexibility can profoundly redirect the hierarchical self‐assembly behaviors in amphiphilic systems. More broadly, this work presents a new strategy to deliberately program hierarchical nanomaterials by designing specific surfactant molecules to act as tunable scaffolds, reactors, and carriers.